An Archaeological Critique of 'Evidence‐based Management': One Digression After Another. (19th March 2015) - Morrell, Kevin; Learmonth, Mark; Heracleous, Loizos
<x xml:space="preserve">Abstract</x> Fundamental problems remain with evidence‐based management. We argue that, rather than being addressed, these problems are treated as digressions. One explanation for this is an ongoing incoherence: the evidence‐based approach relegates narrative to a ghetto category of knowledge, but it is itself a narrative. Moreover, while this narrative is becoming more polished through repetition and selective assimilation of critique, it is also becoming simplified and less interesting. A Foucauldian, archaeological analysis accounts for this development by locating evidence‐based management in a broader historical context. This analysis shows how the roots of incoherence can be informed by older exchanges between evidence and narrative.